ONLINE LEARNING READINESS AND STUDENT STUDY SATISFACTION IN ENGLISH WRITING CLASS DURING THE PANDEMIC (RETAIN, 2023)
This article reports the result of a correlation between online learning readiness and students' study satisfaction and those influences on writing online learning as the success predictor of the students in the pandemic. The participants (n = 30) are 8th-semester students enrolled in writing courses during the pandemic. Students are experienced using various (online) learning platforms to link the learning process. For more reliable data, this research used survey and follow-up interviews to gain in-depth data related to the relation between online learning readiness and students’ study satisfaction as the success predictors of students' who took writing courses during a pandemic. They were asked about their perception of having writing during the pandemic to investigate their OLR and study satisfaction. The results indicated that OLR and SSS are almost significantly related specifically between; students’ study satisfaction and self-directed learning [ r-table .374 > r-count .271], students’ study satisfaction and learner control [r-table .374 > r-count .603] and between students’ study satisfaction and motivation [ r-table .374 > r-count .617]. However, there are no correlation between; students' study satisfaction and computer and internet self-efficacy [ r-table .374 > r-count .271]; and students' study satisfaction and online communication self-efficacy [ r-table .374 > r-count .286]. The interview resulted different opinions between students with high and low scores. Student with high scores students’ study satisfaction stated that OLR is more important than study satisfaction. While student with low scores students’ study satisfaction stated that students' study satisfaction is more important than OLR because it indicates the success of the course program. Keywords: Online learning readiness, study satisfaction, pandemic, writing skill.